Abracadabra. Il potere curativo delle parole tra mito, tradizioni e neuroscienze - Muntoni, Cristina (Milano University Press, 2022)
Sacred texts, myths and traditions worldwide attribute a healing power to words. Abracadabra, the magic word par excellence, is mentioned in the physician's book of Emperor Caracalla as a healing tool, and Gorgias in the 5th century BC compare drugs to words. What is the vision of science? What effect do words have on the brain? This volume addresses in a simple way the theme of the healing power of words both from the point of view of the history of religions, mythology and ethology and from a neuroscientific point of view. Speech produces changes in the activity of the brain that can be the basis of psychotherapy and contribute to the psychophysical wellness of the person in health and disease.